Biological Decontamination of Water Using Non-Thermal Plasma Treatment. (4th January 2017) - Abdel-Fattah, Tarek M; Cetinkaya, Ekrem; Pell, William; Hughes, David; Malik, Muhammad
Abstract : In this study, a low cost nano-second pulsed high voltage power system was used to generate plasma on water surface in a water treatment reactor at the expense of electrical energy. E. coli was inoculated as a model bacterial contaminant in the treatment water. The results of the bacterial counts obtained showed a 65% decrease from 244 colony forming units (CFUs) in the control to 89 CFUs in the plasma treated water that is a significant reduction of the bacterial count. In a separate experiment, methylene blue was mixed with the water as a model chemical decontaminant. The significance of an alternative decontamination method, both cost effective and safe will be an answer to the increasing scarcity of clean water all around the world. This method will especially be useful in developing countries.